ANALYSIS OF CONFIDENCE LEVEL IN ELEMENTARY SCHOOL AGE CHILDREN AT SDN 008 LEMPUNAH, JEMPANG DISTRICT, WEST KUTAI REGENCY - Erin Dasia (Journal of Health, Sport, and Nursing, 2026)
Confidence in elementary school children is a belief in a positive attitude, and an individual's mental ability to understand their potential to act, be independent, make simple decisions, and adapt to the environment and achieve the desired results. Elementary school-age children are a group of 6-12 years old who are experiencing rapid development in various aspects, such as physical, cognitive, social, language, and emotional. This study aims to analyze the level of confidence in elementary school-age children at SDN 008 Lempunah, Jempang District. The study used a quantitative descriptive design with a cross-sectional approach. The sampling technique is consecutive sampling. The sample in this study consisted of 106 students. The instrument in this study is in the form of Lauster's confidence questionnaire, which is compiled based on five indicators of confidence on the Likert scale. Data analysis was carried out univariate to describe the characteristics of respondents and the distribution of student confidence levels. The results showed that most of the respondents were in the high category, namely 61 respondents (57.55%). Furthermore, respondents with low confidence levels amounted to 45 respondents (42.45%). The results of univariate data analysis showed that the confidence level of elementary school-age children at SDN 008 Lempunah was mostly in the high category. The determination of the category is based on the median value as the cut off point.